“Efecto de la adición de semillas de cáñamo (Cannabis sativa ssp. sativa) en la elaboración de un queso fresco” - López Silva, Joselyn Pamela (2024)
Fresh cheese, a food appreciated for its flavor and culinary versatility, is constantly evolving thanks to the search for innovative ingredients. In this context, hemp seeds emerge as a promising option, not only for their exceptional nutritional potential but also for their potential to improve the organoleptic characteristics of foods. The main objective of this research is to elaborate a fresh cheese with the addition of hemp seeds (Cannabis sativa ssp. sativa), in order to determine if there is a nutritional contribution due to the high value of fatty acids, vitamins and antioxidant properties of hemp seeds. Four treatments were evaluated in which different concentrations of hemp seeds were added, a control was included (fresh cheese without the addition of hemp seeds). To determine the best treatment, physical and chemical variables (moisture, total solids, protein, fat, ash, titratable acidity) and sensory variables (appearance, color, flavor, aroma, hardness, general impression) were measured, applying a DBCA experimental design with 3 replications. The best treatment determined was T4 (2,49% of the m/m percentage of hemp seeds in the fresh cheese). After the best treatment was identified, the bromatological and microbiological analyses required by NTE INEN 1528:2012 (General Standard for fresh unripened cheese. requirements) were performed, where the following results were presented: Moisture% 48,09%; Total acidity 0,43%; Total solids 8,36%; pH 6,88 pH units; Dry matter 49,97%; Protein 22,48%; Fiber 1,92%; Fat 24,17%; Organic matter 96,76%; ash 3,24%, in comparison with the control treatment, higher values were presented, especially in variables such as protein content and fat profile. And in the microbiological analysis: Enterobacteriaceae 15 CFU/g; Escherichia coli absent; Staphylococcus aureus absent; Listeria monocytogenes absent; Salmonella absent, which in all parameters are within the ranges established by the standard, therefore, the fresh cheese with the addition of hemp seeds is suitable for human consumption. The analysis of antioxidant capacity gave us as a result the value of 259,57 μmol equ11ivalent of Trolox/ 100 g of sample to the control treatment and to the best treatment of 280,80 equivalent of Trolox/ 100 g of sample, therefore the cheese with the addition of hemp seeds increases the antioxidant capacity of the organism.